The Majelis Ulama’s Fatwa on Freedom of Expression On Social Media: The Perspective of Maqashid Sharia - Arisandy, Danil Putra; Asmuni, Asmuni; Albani Nasution, Muhammad Syukri (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This article criticizes MUI Fatwa Number 24 of 2017 concerning guidelines for naming through social media, wherein the decision of its legal provisions the fatwa has given many restrictions that can be understood as an effort to close the space for freedom of expression and opinion on social media, the impact of which social media users feel afraid and restrained to views. The existence of this fatwa is fundamental because it provides clues regarding the rights of free speech for social media users from an Islamic perspective. This paper uses Jasser Auda's maqasheed sharia approach, namely system theory, as a normative analysis in criticizing fatwas against the interpretation of ghibah behavior, the concept of tabayyun, the public domain in the torso of the general provisions of fatwas. This article argues that the performance of the behavior of the ghibah, the concept of tabayyun, the public domain, in the general conditions of the fatwa body is very influential in the understanding of Islamic law itself towards a direction that is contrary to the purpose of maqasheed sharia, namely the law for the benefit of the people. This is because the interpretation of the fatwa is not ideal for realizing the goal of protecting the human right to opinion for social media users in a country that applies the concept of democracy. This argument is based on the researchers' reading of the MUI Fatwa using a system theory that says the purpose of the law is to achieve the universal benefit, which is inseparable from all points of view of Islamic law. In the end, this article concludes that there is a need to reconstruct the interpretation of the ghibah concept of tabayun, the public domain in the Majelis Ulama’s fatwa.